An engineered 5-helix bundle derived from SARS-CoV-2 S2 pre-binds sarbecoviral spike at both serological- and endosomal-pH to inhibit virus entry. Issue 1 (31st December 2022) - Lin, Xi; Guo, Liyan; Lin, Sheng; Chen, Zimin; Yang, Fanli; Yang, Jing; Wang, Lingling; Wen, Ao; Duan, Yanping; Zhang, Xindan; Dai, Yushan; Yin, Keqing; et al.
ABSTRACT: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and related sarbecoviruses enter host cells by receptor-recognition and membrane-fusion. An indispensable step in fusion is the formation of 6-helix bundle by viral spike heptad repeats 1 and 2 (HR1 and HR2). Here, we report the construction of 5-helix bundle (5HB) proteins for virus infection inhibition. The optimal construct inhibits SARS-CoV-2 pseudovirus entry with sub-micromolar IC50. Unlike HR2-based peptides that cannot bind spike in the pre-fusion conformation, 5HB features with the capability of binding to pre-fusion spike. Furthermore, 5HB binds viral HR2 at both serological- and endosomal-pH, highlighting its entry-inhibition capacity when SARS-CoV-2 enters via either cell membrane fusion or endosomal route. Finally, we show that 5HB could neutralize S-mediated entry of the predominant SARS-CoV-2 variants and a wide spectrum of sarbecoviruses. These data provide proof-of-concept evidence that 5HB might be developed for the prevention and treatment of SARS-CoV-2 and other emerging sarbecovirus infections.